Konsumsi Vitamin D dan Zink dengan Kejadian Stunting pada Anak Sekolah SD Negeri 77 Padang Serai Kota Bengkulu - Mia Lestari Putri; Betty Yosephin Simanjuntak; Tetes Wahyu W. (Politeknik Kesehatan Tanjung Karang, 2018)
Deficiency of micronutrition is one of the factors which influence the deficiency of chronic nutrition. Deficiency of vitamin D can lower the absorption of calcium and phosphor. Deficiency of zinc can stunt children because zinc has the main role on growth acceleration period both before and after their birth. One of the impacts of chronic nutrition deficiency is the descending of growth acceleration or linear disturbance so the children fail on gaining height potency which causes the children to become stunt. This research is purposed to know the relation of consuming vitamin D and zinc with the stunting of the students of SD Negeri 77 Padang Serai Kota Bengkulu. This research is kind of analytical observation research with a cross-sectional approach which is done from January to April in SD Negeri 77 Padang Serai Kota Bengkulu. There are 80 subjects in this research. The variable which is observed about consuming vitamin D, consuming zinc and stunting the analysis used a chi-square test. In this research, the data is collected by using an interview with semi FFQ form (Food Frequency Questionnaire). The result of this research shows that there is a relation between consuming zinc and stunting to the students of SD Negeri 77 Padang Serai Kota Bengkulu, however, there is no relation between consuming vitamin D and stunting to the students of SD Negeri 77 Padang Serai Kota Bengkulu.